The advanced methods of hyperhidrosis treatment using Botulinum toxin - Blicharz, Agnieszka; Marzęda, Magdalena; Swatko, Tomasz; Stachura, Tomasz; Rybak, Natalia (Journal of Education, Health and Sport, 2022)
Introduction and purpose: Sweating plays an important role in the mechanism of human thermoregulation. A state in which the amount of sweat produced exceeds the physiological demand is called hyperhidrosis. About 4.8% of the population complains of this condition. The inconvenience of excessive sweat production significantly decrease the standard of living of patients suffering from this disorder. Nowadays, botulinum toxin injections are increasingly being used as a therapy for excessive sweating. Brief description of the state of knowledge: Botulinum toxin is an exotoxin produced by the bacteria Clostridium botulinum . It is now considered one of the most potent poisons found in nature. Thanks to research conducted since the 1970s, the positive effects of using TB to treat strabismus, eyelid spasm, torticollis and other conditions associated with excessive muscle spasticity have been noted. This discovery coused a flood of subsequent research on the use of botulinum toxin in medicine and cosmetology. It derives its features from inhibiting the release of Acetylcholine in nerve endings, which prevents muscle contraction. Acetylcholine is the main transmitter of the sympathetic nervous system, which innervates the sweat glands. Thanks to these features, botulinum toxin has begun to be widely used to treat excessive sweating. Summary: Excessive sweating is very often resistant to treatment attempts with iontophoresis or external substances. Botulinum toxin injections into the areas most affected by the condition, which are most often the hands, feet, armpits, bring significant improvement in patients. Currently, research is being conducted about the use of botulinum toxin in other areas of the body.